Fumigant Nematicides Registered for Vegetable Crop Use in Florida - Joseph W. Noling (EDIS, 2013)
This 3-page fact sheet lists of multispectrum fumigant nematicides currently registered for use on different Florida crops (Table 1); their maximum rates and specific details for field application (Table 2); and a generalized summary of maximum use rate and relative effectiveness of various soil fumigants for nematode, soilborne disease, and weed control in Florida (Table 3). Written by J. W. Noling and published by the UF Department of Entomology and Nematology, January 2013.